Reversal of beta-cell suppression in vitro in pancreatic islets isolated from nonobese diabetic mice during the phase preceding insulin-dependent diabetes mellitus. - Strandell, E (1990)
Insulin-dependent diabetes mellitus (IDDM) is characterized by a progressive autoimmune destruction of the pancreatic beta-cells. One of the best-suited animal models for IDDM is the nonobese diabetic (NOD) mouse. In this investigation pancreatic islets were isolated from female NOD mice aged 5-7, 8-11, and 12-13 wk and examined immediately (day 0) or after 7 d of culture (day 7). The mice showed a progressive disturbance in glucose tolerance with age, and a correspondingly increased frequency of pancreatic insulitis. Islets isolated from the oldest mice often contained inflammatory cells on day 0, which resulted in an elevated islet DNA content. During culture these islets became depleted of infiltrating cells and the DNA content of the islets decreased on day 7. Islets of the eldest mice failed to respond with insulin secretion to high glucose, whereas a response was observed in the other groups. After culture all groups of islets showed a markedly improved insulin secretion. Islets from the 12-13-wk-old mice displayed a lower glucose oxidation rate at 16.7 mM glucose on day 0 compared with day 7. Islet (pro)insulin and total protein biosynthesis was essentially unaffected. In conclusion, islets obtained from 12-13-wk-old NOD mice exhibit an impaired glucose metabolism, which may explain the suppressed insulin secretion observed immediately after isolation. This inhibition of beta-cell function can be reversed in vitro. Thus, there may be a stage during development of IDDM when beta-cell destruction can be counteracted and beta-cell function restored, provided the immune aggression is arrested.